Family Experiences in Caring for Covid-19 Positive at Home: Phenomenology Study - Fradianto, Ikbal; Mita, Mita; Yulanda, Nita Arisanti; Rahmawati, Nadia; Putri, Triyana Harlia; Andriyanto, Arief (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Covid-19, a global problem since 2019, has significantly increased in Indonesia since early 2020. Government policies restrict patients from outside activities, making home care a unique experience. This study aims to understand families' experiences in caring for positive Covid-19 patients. Methods: The method used is qualitative with a phenomenological study approach. There were 12 participants in this study with the criteria of accompanying patients who experienced Covid-19 <1 year and these companions cared for patients at home. The sampling technique used was purposive sampling, with in-depth interviews of 30-45 minutes and recorded and recorded. The data analysis technique used is the collaizi method. Results: The results of the study obtained six themes, namely understanding Covid-19 Disease, Information Sources for Covid-19 Treatment, Treatment Considerations, Psychological Burden, Difficulties in Home Care, and Social Support. Conclusions: This study found six themes related to family experience in caring for Covid-19 patients, so that the role of the family and social community is very important in caring for Covid-19 patients in dealing with changing conditions and situations.